Hell's gate : a thriller - Schutt, Bill; Finch, J. R. (Suspense fiction writer) (Schutt, Bill. R. J. MacCready novel., 2016)
"1944. As war rages in Europe and the Pacific, Army Intel makes a shocking discovery: a 300-foot Japanese sub marooned and empty, deep in the Brazilian interior. A team of Army Rangers sent to investigate has already gone missing. Now, the military sends Captain R.J. MacCready, a wisecracking, brilliant scientific jack-of-all-trades to learn why the Japanese are there-and what they're planning. Parachuting deep into the heart of Central Brazil, one of the most remote regions on the planet, Mac is unexpectedly reunited with his hometown friend and fellow scientist Bob Thorne. A botanist presumed dead for years, Thorne lives peacefully with Yanni, an indigenous woman who possesses mysterious and invaluable skills. Their wisdom and expertise are nothing short of lifesaving for Mac as he sets out on a trail into the unknown. Mac makes the arduous trek into an ancient, fog-shrouded valley hidden beneath a 2000-foot plateau, where he learns of a diabolical Axis plot to destroy the United States and its allies. But the enemy isn't the only danger in this treacherous jungle paradise. An even darker force is on the prowl, attacking at night and draining the blood of livestock and human prey. Mac has to uncover the source of this emerging biological crisis and foil the enemy's plans ... but will he be in time to save humanity from itself?"--